Accounting Information Systems: Scientific Production and Trends in Research - Monteiro, Albertina Paula (2022)
This paper aims to provide a state-of-the-art overview in research on Accounting Infor- mation Systems, analyzing scientific production characteristics and identifying this topic research trends. A quantitative bibliometric analysis is conducted on papers specifically focused on Account- ing Information Systems, published in journals indexed on Web of Science database. The research methodology and design were based on an inductive approach of a set of studies with the objective of theoretical development in the field of investigation. We found 144 articles on this subject. The first article was published in 1973. However, most papers were published during the last 10 years al- though the highest interest in Accounting Information Systems study among scholars concentrates on a short period, which is around 2020. We identify three research topics, as the following research trends: (1) the Accounting Information System impact in the organization (e.g., performance, inno- vation, reorganization of activities, information reporting); (2) the Accounting Information System Construction, (3) the importance of implementation of the Accounting Information System in small and medium-sized enterprises and Public-Sector; and (4) the factors that contribute to Accounting Information System efficiency/quality. These themes fit into a theoretical framework, in which agency and contingency theory are highlighted. In addition, by promoting the analysis of strict bibliometric tools, we also identified authors, journals, organizations and countries/regions that contributed most to the development of the investigation in this research topic. The results of this research add insights to the existing literature and serve as a guide for future research in Accounting Information Systems context, as well as help organizations, public, private and governments to establish their strategies in this area.